The Effect of Voice Ambulatory Biofeedback on the Daily Performance and Retention of a Modified Vocal Motor Behavior in Participants With Normal Voices - Van Stan, Jarrad H. (J Speech Lang Hear Res, 2015)
PURPOSE: Ambulatory biofeedback has potential to improve carryover of newly established vocal motor behaviors into daily life outside of the clinic and warrants systematic research that is lacking in the literature. This proof-of-concept study was designed to establish an empirical basis for future work in this area by formally assessing whether ambulatory biofeedback reduces daily vocal intensity (performance) and the extent to which this change remains after biofeedback removal (retention). METHOD: Six participants with normal voices wore the KayPENTAX Ambulatory Phonation Monitor for 3 baseline days followed by 4 days with biofeedback provided on odd days. RESULTS: Compared to baseline days, participants exhibited a statistically significant decrease in mean vocal intensity (4.4 dB) and an increase in compliance (16.8 percentage points) when biofeedback was provided above a participant-specific intensity threshold. After biofeedback removal, mean vocal intensity and compliance reverted back to baseline levels. CONCLUSIONS: These findings suggest that although current ambulatory biofeedback approaches have potential to modify a vocal motor behavior, the modified behavior may not be retained after biofeedback removal. Future work calls for the testing of more innovative ambulatory biofeedback approaches on the basis of motor control and learning theories to improve retention of a desired vocal motor behavior.